Measuring water use with remote sensing. - Siddiqi, Yasmin (Water Briefs., 2017)
Using remote sensing technology, for the first time water productivity can be measured right down to the farm level. For years, the limitation has always been the lack of data. With remote sensing technology, this will no longer be an issue.